Sistem Informasi Pemasaran Busana Syar’i dengan Penerapan Customer Relationship Management (CRM) Berbasis Web - Yuda Irawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Toko Cahaya Sunnah is a business that produces and sells syar'i clothing. In its business development, Toko Cahaya Sunnah keep trying to expand its market target to out of town even all of Indonesia. To achieve its goal, Toko Cahaya Sunnah requires website. Currently in Toko Cahaya Sunnah in making sales report is still manual using excel application so that data processing of sales report still running slow and not yet detailed. Currently Toko Cahaya Sunnah does not have any special activities or strategies that handle marketing, product marketing is done in a conventional manner by providing customers with information about places, features and products to other potential customers. Ineffective information dissemination prevents customers from knowing the latest information in the Sunnah Light Store thus affecting customers to switch to other stores. With the website using the method of Customer Relationship Management (CRM) then the data storage process can be more accurate and stored neatly and making sales reports will be fast and timely and delivery of promotional information will be faster and response to sales will be faster. Keywords: Information System, Customer Relationship Management (CRM), Web